Women Having Abortion in Urban Nepal: 2005 and 2010 Compared - Thapa, Shyam; Neupane, S; Basnett, I; Read, E (Kathmandu University Medical Journal, 2013)
Background The use of abortion services at the Maternity Hospital clinic, the largest public sector abortion clinic in Nepal, has risen over the years. Whether the profile of the clients, reasons for abortion, and contraceptive use have changed are not known and need to be investigated. Objectives This paper evaluates changes between 2005 and 2010 in the socio-demographic profile of abortion users, reasons for seeking abortion, and contraceptive use of two cohorts of women who had first-trimester abortion at the Maternity Hospital. Methods We used data from two similar surveys conducted in 2005 and 2010 among 672 and 392 women, respectively, who obtained first-trimester surgical abortion in a large public sector clinic. We analyzed trend data in service utilization and carried out a cost analysis. Results The number of women having abortions has steadily increased over the years, and cumulatively about 19,800 women have received services. The profile of the clients at this clinic has remained essentially the same between 2005 and 2010. The typical users of abortion services at the clinic were 27 years old with two living children, mostly married, with the majority not wanting to have more children. About half of them used a contraceptive method—mostly condoms, withdrawal, the pill and rhythm—in the month of unintended pregnancy, suggesting failures with these methods. Health concerns, dislike of available methods, and perceived low risk of pregnancy were common reasons for not using a contraceptive method. Conclusion Despite increases in the number of clients, the socio-demographic profile of the abortion clients has remained similar over the years. The linkage between the abortion and family planning clinics needs to be strengthened. Kathmandu University Medical Journal | VOL.10 | NO. 3 | ISSUE 39 | JUL- SEP 2012 | Page 8-13 DOI: http://dx.doi.org/10.3126/kumj.v10i3.8010